2013
DOI: 10.1017/s1755267212001108
|View full text |Cite
|
Sign up to set email alerts
|

First report of Pararotalia calcariformata from the Hatay coastline (Turkey—north-eastern Mediterranean)

Abstract: engin meric ‚ 1 , mehemet baki yokes 2 , kadiko ¤y niyazi avsar 3 , elmas kirki-elmas 4 , feyza dinc ‚er 5 , selahattin unsal karhan 5 , evrim kalkan 6 and volkan demir 7 1 Moda Hüseyin Bey Sk. No. 15/4, Alien benthic foraminiferal assemblages of Samandag and Yayladagı coasts (Hatay, Turkey) have been investigated. 41 genera and 58 species of benthic foraminifers were identified and Indo-Pacific originated alien species were found to dominate the foraminiferal assemblage. Pararotalia calcariformata which shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…A comparison of the morphology of the Levantine species with this description confirms that the assignment of the invasive species to Pararotalia spinigera is incorrect, because a keel and deep septal interlocular space are clearly present among the Levantine specimens. Our analysis also confirms that the specimens we examined have similar appearance as those reported by [ 32 ] from Hatay, Turkey. Therefore, we here conclude that morphologically, the invasive species shows most affinity with the concept of P .…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…A comparison of the morphology of the Levantine species with this description confirms that the assignment of the invasive species to Pararotalia spinigera is incorrect, because a keel and deep septal interlocular space are clearly present among the Levantine specimens. Our analysis also confirms that the specimens we examined have similar appearance as those reported by [ 32 ] from Hatay, Turkey. Therefore, we here conclude that morphologically, the invasive species shows most affinity with the concept of P .…”
Section: Resultssupporting
confidence: 90%
“…Other studies confirmed the proliferation of the species P . calcariformata after 1994, identifying large populations ranging from the southernmost Israeli coast [ 30 , 31 ] to southern Turkey [ 32 ]. All localities where this species has been reported up to now in the literature as well as through our investigations in the eastern Mediterranean are given in S1 Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations